A Case Report on UTI w.s.r. Mutrakriccha in Children - Kaushik, Jyoti; Sharma, Rakesh (International Research Journal of Ayurveda & Yoga, 2020)
Urinary tract infection (UTI) is one of the most common paediatric infections that distresses the child and concerns the parents. It occurs in 1% of boys and 3-8 % of girls, however incidence varies with age. E. coliis the most prevalent etiological agent followed by Klebsiella spp. and Proteus spp. UTI comes under the broad term of Mutrakriccha as both have similar characteristic features like Dysuria (Sarujamutrta),Yellow discolouration of urine (Peetamutrta), Hematuria (Saraktamutrta), Burning micturition (Sadahamutrta), Urgency and frequency (Muhurmuhur Mutrta). The present case report deals with UTI in an 8 years old female child. She was treated with Ayurvedic formulations mentioned in classical texts for Mutrakriccha. Marked reduction in the symptoms was observed after 15 days of treatment. The patient was in regular follow up with no re-admission for repeat UTI.